Cerebral Palsy Parents’ Knowledge, Attitude, and Behavior at Dr. Hasan Sadikin General Hospital Bandung 2014 - Maria Christina Shycha Moenardi; Ellyana Sungkar; Dewi Hawani (Althea Medical Journal, 2020)
Background: Cerebral palsy (CP) as a non-progressive syndrome of motor function and posture disturbance is caused by the abnormality or damage on the brain during its development. Children with CP usually have motor, sensory, communication, and intellectual disturbances. Medical rehabilitation is important; however, the environmental aspect is also crucial for their development. Parents as their caregivers may have good knowledge to assist their children during rehabilitation. This study aimed to explore the knowledge, attitude, and behavior among parents with CP children.Methods: This study was descriptive quantitative study and conducted at the Physical Medicine and Rehabilitation Clinic of Dr. Hasan Sadikin General Hospital Bandung during September to October 2014. Parents of CP children were asked to complete a questionnaire that was specifically designed for this study after their consent was obtained.Results: From a total of 31 parents, 51.6% had good knowledge about CP; 58.1% had good attitude toward CP children, and 51.6% had good behavior while taking care of their children.Conclusions: The majority of parents with CP children have good knowledge, attitude, and behavior towards CP children. The knowledge of risk factors of cerebral palsy are poor, therefore, it is necessary for doctors and therapists to provide more education sessions on the risk factors and other related topics about cerebral palsy.